2022
DOI: 10.3390/f13050644
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Effects of Forest Litter on Seedling Establishment

Abstract: Litter plays an important role in seedling establishment (emergence, survival, and early growth). Here, we performed a meta-analysis on 404 datasets from 33 independent studies to analyze the effects of litter cover on seedling emergence, survival, height, and biomass (root, stem, leaf, and total). Each dataset was stratified according to experimental conditions, litter type (broadleaf versus needle litter), litter amount (thickness), and seed size. The results showed that litter cover had an overall negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
1
2
0
1
Order By: Relevance
“…However, partly supporting our hypothesis that litter could significantly affect each stage, the present results indicated that litter did not directly affect the seed stage and that vegetation factors contributed more than environmental factors to the effect of litter (Figure 7). Differences in litter effects between vegetation types support previous findings (Loydi et al, 2013; Wang et al, 2022; Xiong & Nilsson, 1999), with higher effects on woody plants than grasses and negative effects on early vegetation growth than the latter.…”
Section: Discussionsupporting
confidence: 87%
“…However, partly supporting our hypothesis that litter could significantly affect each stage, the present results indicated that litter did not directly affect the seed stage and that vegetation factors contributed more than environmental factors to the effect of litter (Figure 7). Differences in litter effects between vegetation types support previous findings (Loydi et al, 2013; Wang et al, 2022; Xiong & Nilsson, 1999), with higher effects on woody plants than grasses and negative effects on early vegetation growth than the latter.…”
Section: Discussionsupporting
confidence: 87%
“…En estos bosques, el mantenimiento de la biodiversidad es posible gracias a los incendios que liberan espacio, nutrientes y luz para la regeneración del arbolado (Rodríguez-Trejo & Fulé, 2003. Por ejemplo, un metaanálisis que incluyo 33 estudios mostró que una capa gruesa de hojarasca puede disminuir la germinación (Wang et al 2022), aunque este efecto depende de la fuente de la hojarasca y las especies que se ponen a germinar (Camacho-Cruz et al 2000). En el paraje de El Fresno se registró que el grosor de la hojarasca era 13 veces más bajo en la severidad alta y 4 veces más bajo en la severidad media de incendio en comparación con el bosque no quemado, mientras que en baja severidad se detectó un grosor de la hojarasca similar al del bosque no quemado (León-Carvajal 2021).…”
Section: Discussionunclassified
“…In contrast to the effect of bryophyte carpets, which varied according to the bryophyte stature, litter dynamics had a constantly negative impact on seedling persistence. A thick and dynamic litter layer, which usually accumulates on the forest soil surface, might hinder the seeds from reaching the soil for germination (Wang et al, 2022) or prevent seedling emergence (Knapp and Smith, 1982;Simard et al, 2003).…”
Section: Discussionmentioning
confidence: 99%